STANDARDIZATION OF FORENSIC EVIDENCE, ITS PROCUREMENT, PRESERVATION AND PRESENTATION IN COURT USING FBI’s TECHNIQUES BY FIA: Dr Aftab Ahmad Malik, Engr. Mujtaba Asad ,Waqar Azeem - Malik, Engr. Mujtaba Asad; Malik, Waqar Azeem (International Journal for Electronic Crime Investigation, 2020)
Abstract The purpose of this paper is to present the some feasible standards used by US Federal Bureau of investigation (FBI) to enable Federal Investigation Agency (Pakistan) to enhance the authenticity of evidence and its consistency with the existing law. There are examples of several hundred cases, where the courts refused to punish the offender due to unauthentic inconsistent or naive evidence. The investigator is normally responsible to procure and preserve the forensic evidence to strengthen the case of the prosecutor. The investigator has follow up the legal procedure, technically in technically correct manner and consistent with provisions of Law, circumstantial and oral evidence. The inherent deficiencies and faults render the forensic evidence invalid sometimes and no use in the court. The approach of the paper is to standardise and synchronise the working as for as dealing with forensic evidence is concerned. The FBI provides very useful methodologies for procuring evidence from the sconce of offence, forensic services, examination of evidence, rendering forensic evidence,